TAFSIR AYAT – AYAT DAKWAH - Kusnadi Kusnadi (LP2M IAIM Sinjai, 2020)
The word da'wah is a term that is quite popular in Islamic scholarship. Da'wah is also a word that has many synonym variants whose substance is generally the same but has different implications. In the study of da'wah science, the term